Effect of Elateriospermum tapos blume in ameliorating development programming of maternal obesity on female offspring Sprague Dawley rats through mesolimbic reward pathway - Zainal Abidin, Azrina (2022)
Early exposure to a high-fat diet increases the risk of obesity in later life. Recent animal studies have revealed that these offspring have a greater preference for fat, raising the possibility that prenatal exposure to high-fat foods alters the central reward system, increasing the desire to eat excessive amounts of palatable foods. Elateriospermum tapos (E. tapos) is a plant with a high phenolic and flavonoid content that has been shown to aid treatment of obesity in animal studies, which led to the hypothesise of E. tapos has the potential to prevent obesity among offspring as well. The present study has determined the effect of E.tapos in improving the developmental programming of maternal obesity on the female offspring's mesolimbic reward pathway. Throughout the study, the effect of E. tapos supplementation in obese rats before pregnancy on the female offspring’s body weight, food intake, liver profile, kidney profile, lipid profile, stress hormone level, organ histology, cognitive effect, and the expression of mu-opioid receptor (MOR) as well as elements of the dopamine pathway; tyrosine hydroxylase (TH), dopamine receptor 2 (DR2) and the dopamine active transporter (DAT) were examined. A rat model of maternal obesity was generated using a high fat and cafeteria diet (HFCD) prior to and throughout pregnancy and lactation. Six rats out of 30 female Sprague-Dawley rats were assigned to the normal diet group. The remaining rats were fed with HFCD to generate obesity for 5 weeks. The obese rats were further divided into 4 groups of parent female (Dams); 1; Dams Negative Control (DNC, normal saline only), 2; Dams Positive Control (DPC, Orlistat drug 200mg/kg), 3; Dams Treatment 1 (DTX1, E. tapos seed 200mg/kg) and 4; Dams Treatment 2 (DTX2, E. tapos shell 200mg/kg) for 6 weeks daily before mating. The weaning offspring were then designated into 6 groups according to their dam’s group (n = 6/group). Memory tasks for object and place recognition were conducted at 8th weeks of age. The offspring were culled at the 12th weeks of age for their organs and blood. The mesolimbic proteins were analyzed through the Western blot procedure. The OTX2 group showed a decrease in weight gain, calorie intake, triglyceride, alanine aminotransferase, creatinine, Adrenocorticotropic and cortisol hormone level compared to ONC. Histological examination showed that liver and retroperitoneal white adipose tissue of OTX1 and OTX2 groups were comparable with the OND group. In memory tasks, OTX2 showed a significant increase in exploration rate in place test as compared to the ONC group. Finally, the MOR, TH, DR2 and DAT proteins in the mesolimbic region were found to be decreased in the ONC group and treatment with E.tapos had increased the proteins comparable with the normal diet group. Study showed that E.tapos seed and shell had ameliorated the changes in protein expression of dopamine and opioid pathways in offspring exposed to HFCD. Consequently, obesity-related parameters were normalized back to the normal level comparable to the normal diet group. This study highlights E. tapos seed and shell as an anti-obesity agent through the regulation of the mesolimbic pathway.